Loss of dendrite stabilization by the Abl-related gene (Arg) kinase regulates behavioral flexibility and sensitivity to cocaine - Gourley, Shannon L. (National Academy of Sciences, 2009)
Adolescence is characterized by increased vulnerability to developing neuropsychiatric disorders and involves a period of prefrontal cortical dendritic refinement and synaptic pruning that culminates in cytoskeletal stabilization in adulthood. The Abl-related gene (Arg) acts through p190RhoGAP to inhibit the RhoA GTPase and stabilize cortical dendritic arbors beginning in adolescence. Cortical axons, dendrites, and synapses develop normally in Arg-deficient (arg(−/−)) mice, but adult dendrites destabilize and regress; thus, arg(−/−) mice present a model of adolescent-onset dendritic simplification. We show that arg(−/−) mice are impaired in a reversal task and that deficits are grossly exacerbated by low-dose cocaine administration. Although ventral prefrontal dopamine D2 receptor levels predict “perseverative” error counts in wild-type mice, no such relationship is found in arg(−/−) mice. Moreover, arg(−/−) mice are insensitive to the disruptive effects of the D2/D3 antagonist haloperidol in reversal but show normal sensitivity to its locomotor-depressant actions. Arg deficiency and orbitofrontal cortical Arg inhibition via STI-571 infusion also enhance the psychomotor stimulant actions of cocaine. These findings provide evidence that stabilization of dendritic structure beginning in adolescence is critical for the development of adaptive and flexible behavior after cocaine exposure.